Change in the North Sea ecosystem from the 1970s to the 2010s: great skua diets reflect changing forage fish, seabirds, and fisheries. (10th December 2018) - Church, Gabriella E; Furness, Robert W; Tyler, Glen; Gilbert, Lucy; Votier, Stephen C
Abstract: Understanding anthropogenic impacts are crucial to maintain marine ecosystem health. The North Sea has changed in recent decades, largely due to commercial fishing and climate change. Seabirds can act as useful indicators of these changes. By analyzing n  = 20 013 pellets and n  = 24 993 otoliths regurgitated by great skuas Stercorarius skua in northern Scotland over five decades from the 1970s to the 2010s (in 36 years 1973–2017), we reveal how the diet of this top predator has changed alongside the changing North Sea ecosystem. Sandeels Ammodytes spp. were the most common dietary item during the 1970s, but became virtually absent from the 1980s onward. Discarded whitefish dominated skua diets from the 1980s to the present day, despite long-term declines in North Sea discard production. However, the discarded fish eaten by great skuas has become smaller and the species composition changed. Skua pellets only rarely contained avian prey in the 1970s but this increased during the 1980s, and fluctuated between 10% and 20% from the 1990s to 2010s. There have also been changes in the avian prey in the diet—black-legged kittiwakes Rissa tridactyla generally being replaced by auks Alcid spp. and northern fulmars Fulmarus glacialis. The Shetland marine ecosystem has experienced steep declines in sandeel stocks and in seabirds that feed on them. Great skuas have been able to prey switch to respond to this change, supported by abundant discards, enabling them to maintain a favourable population status while other seabird species have declined.